Advances in Trop-2 targeted antibody-drug conjugates for breast cancer: mechanisms, clinical applications, and future directions - Tong, Yujun; Fan, Xiaobing; Liu, Huan; Liang, Tiantian (Frontiers in Immunology, 2024)
Breast cancer remains a leading cause of cancer-related deaths among women worldwide, highlighting the need for novel therapeutic strategies. Trophoblast cell surface antigen 2 (Trop-2), a type I transmembrane glycoprotein highly expressed in various solid tumors including all subtypes of breast cancer, has emerged as a promising target for cancer therapy. This review focuses on recent advancements in Trop-2-targeted antibody-drug conjugates (ADCs) for breast cancer treatment. We comprehensively analyzed the structure and mechanism of action of ADCs, as well as the role of Trop-2 in breast cancer progression and prognosis. Several Trop-2-targeted ADCs, such as Sacituzumab Govitecan (SG) and Datopotamab Deruxtecan (Dato-DXd), have demonstrated significant antitumor activity in clinical trials for both triple-negative breast cancer (TNBC) and hormone receptor-positive/HER2-negative (HR+/HER2-) breast cancer. We systematically reviewed the ongoing clinical studies of these ADCs, highlighting their efficacy and safety profiles. Furthermore, we explored the potential of combining Trop-2-targeted ADCs with other therapeutic modalities, including immunotherapy, targeted therapies, and small molecule inhibitors. Notably, Trop-2-targeted ADCs have shown promise in reprogramming the tumor microenvironment through multiple signaling pathways, potentially enhancing antitumor immunity. This review aims to provide new insights and research directions for the development of innovative breast cancer therapies, offering potential solutions to improve treatment outcomes and quality of life for breast cancer patients.